Associations Between Spousal Relationship, Husband Involvement, and Postpartum Depression Among Postpartum Mothers in West Java, Indonesia - Pebryatie E. (2023)
Introduction: Indonesia is actively promoting husband involvement in maternal health care, since it has been claimed to impact the wellbeing of mothers. This study aims to investigate the extent to which spousal relationship, husband involvement, and maternal health behavior affect postpartum depression among Indonesian mothers. Method: A survey was carried out among 336 postpartum mothers who received maternal care in 27 independent midwifery clinics in 7 regions of West Java Province, Indonesia. The measurement model of husband involvement comprising 4 dimensions, namely maternity care engagement, instrumental support, emotional support, and informational support were developed and validated using confirmatory factor analysis. The Quality of Marriage Index (QMI) and the Edinburgh Postnatal Depression Scale (EPDS) were also validated and used to measure spousal relationship and postpartum depressive symptoms. A structural equation model was specified to examine the association between spousal relationship, husband involvement, maternal healthy behavior, and postpartum depression. Results: The study confirms the assumption that the quality of the spousal relationship could determine husband’s involvement during pregnancy, childbirth, and postpartum (γ =.60, P <.001), eventually leading to better maternal healthy behavior (γ =.015, P <.001) and a decrease in postpartum depressive symptoms among mothers (γ = −.21, P <.001). Conclusions: The study results suggest the needs to promote comprehensive husband involvement to enhance the wellbeing of mothers. This can be achieved through couple interventions at the community level and the inclusion of a supportive role for husbands in the maternal and childcare guidebook offered during ANC visits.